Rethinking the components, coordination, and management of the U.S. Environmental Protection Agency laboratories (National Academies Press, 2014)
"The Environmental Protection Agency (EPA) applies scientific results that have been provided by various parts of its own organization and by external organizations. The agency requires substantial high-quality inhouse scientific expertise and laboratory capabilities so that it can answer questions related to regulation, enforcement, and environmental effects of specific chemicals, activities, and processes. It is also usually faced with situations in which research or analytic work is time-critical, so it maintains dedicated laboratory staff and facilities that can respond quickly to such needs. In recent years, EPA has made several changes to improve the efficiency and effectiveness of its laboratories, such as the designation of national program directors to align the work of research laboratories with the needs of the agency's regulatory program offices. The agency is currently undertaking an integrated evaluation of it laboratories to enhance the management effectiveness and efficiency of its laboratory enterprise and to enhance its capabilities for research and other laboratory-based scientific and technical activities. The results of EPA's evaluation are expected to include options for colocation and consolidation of laboratory facilities. Rethinking the Components, Coordination, and Management of U.S. Environmental Protection Agency Laboratories assesses EPA's highest-priority needs for mission-relevant laboratory science and technical support, develops principles for the efficient and effective management of EPA's laboratory enterprise to meet the agency's mission needs and strategic goals, and develops guidance for enhancing efficiency and effectiveness now and during the next 10 years. EPA's laboratories play a vital role in the agency's work. The findings and recommendations of this report will help EPA to develop an implementation plan for the laboratory enterprise."--Publisher's description